2019
DOI: 10.1111/mpp.12814
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of auxin signalling promotes rice susceptibility to Rice black streaked dwarf virus infection

Abstract: Summary Auxin plays a fundamental role in plant growth and development, and also influences plant defence against various pathogens. Previous studies have examined the different roles of the auxin pathway during infection by biotrophic bacteria and necrotrophic fungi. We now show that the auxin signalling pathway was markedly down‐regulated following infection of rice by Rice black streaked dwarf virus (RBSDV), a dsRNA virus. Repression of the auxin receptor TIR1 by a mutant o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
59
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(68 citation statements)
references
References 40 publications
1
59
0
Order By: Relevance
“…Previous studies have shown that auxin signaling play a negative role in the defense response against RBSDV infection. Overexpression of the auxin signaling repressors OsIAA20 and OsIAA31 has been demonstrated to be conducive to RBSDV infection [ 25 ]. In this study, LOC_Os03g43410 and LOC_Os05g43920 were found to be auxin response factors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that auxin signaling play a negative role in the defense response against RBSDV infection. Overexpression of the auxin signaling repressors OsIAA20 and OsIAA31 has been demonstrated to be conducive to RBSDV infection [ 25 ]. In this study, LOC_Os03g43410 and LOC_Os05g43920 were found to be auxin response factors.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies on rice plants defense against RBSDV mainly focused on RNAi [ 21 , 22 ] and plant hormone signaling pathways [ 23 ]. For instance, the jasmonate (JA) and auxin signaling pathways enhance plant defense against RBSDV [ 24 , 25 ], whereas brassinosteroid (BR) and abscicic acid (ABA) pathways facilitated the viral infection [ 25 , 26 ]. However, the role of host DNA methylation in RBSDV infection still remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Auxin signalling and plant defence have long been known to be antagonistic towards each other (Iglesias et al , ; Kidd et al , ; Fu et al , ; Mutka et al , ; Zhang et al , ). However, previous studies have reported that plant resistance to the necrotrophic fungi Plectosphaerella cucumerina and Botrytis cinerea , as well as to the necrotrophic oomycete pathogen Pythium irregulare (Tiryaki and Staswick, ) was impaired by repressing auxin signalling as a result of pharmacological interference or mutation construction that affected the auxin pathway (Llorente et al , ).…”
Section: Discussionmentioning
confidence: 99%
“…A very recent study offered novel insights into the crosstalk regulatory mechanisms of auxin, JA and ROS pathway in rice-RBSDV interaction. Using various auxin signaling mutants, auxin was proved to play a positive role in rice immunity against RBSDV, during this process, JA and ROS pathway also contributed to this defense (Zhang et al 2019). Thus, it is apparent that the signaling interactions among multiple phytohormones are rather common in rice antiviral defense response.…”
Section: Multiple Layers Modulation Of Rice Immunitymentioning
confidence: 99%
“…1). In recent years, several studies have also provided insights into how defense signaling networks and defense signal molecules intersect with rice-virus interactions (Lee et al 2010;Wu et al 2015;Wang et al 2016;Wu et al 2017;Yao et al 2019;Zhang et al 2019). A deeper understanding of plant antiviral immunity and viral pathogenesis may facilitate innovative biotechnological, genetic and breeding approaches for crop protection and improvement.…”
Section: Introductionmentioning
confidence: 99%